Evaluation of a constant rate intravenous infusion of dexmedetomidine on the duration of a femoral and sciatic nerve block using lidocaine in dogs - Marzia Stabile; Luca Lacitignola; Claudia Acquafredda; Annalaura Scardia; Antonio Crovace; Francesco Staffieri (Frontiers in Veterinary Science, 2023)
ObjectivesThis study investigated the effects of 1 μg/kg/h intravenous constant rate infusion (CRI) of dexmedetomidine on the sensory and motor blockade for femoral and sciatic nerve blocks in dogs undergoing stifle surgery.Materials and methodsClient-owned dogs referred for stifle surgery were enrolled in this prospective, randomized, blinded study. Dogs were pre-medicated with acepromazine (0.005–0.01 mg/kg intramuscularly, IM); anesthesia was induced with propofol intravenously and maintained with isoflurane in a mixture of air and oxygen. Electrolocation-guided sciatic and femoral nerve blocks with lidocaine 2% (0.15 mL/kg) were performed using the parasacral and lateral pre-iliac approaches, respectively. After performing local block, a systemic infusion of saline solution (group C) or dexmedetomidine (group D) was started at a CRI at 1 ml/kg/h and continued until the end of surgery. Dexmedetomidine was infused at a dose of 1 μg/kg/h. Respiratory and hemodynamic variables were recorded during surgery. Sensory and motor blockade was evaluated by response to pinching the skin innervated by the sciatic/femoral nerves, with forceps and by observing the dogs' ability to walk and testing proprioception at 30, 60, 120, 180, and 240 min after extubation. Analgesia was monitored with SF-GCPS. Methadone IM was administered as rescue analgesia. Intraoperative data were analyzed by analysis of variance, while postoperative data were analyzed by the independent two-tailed t-test and a Kaplan–Meier test (p < 0.05).ResultsTwenty dogs were included in this study (10/group). A significant difference in the recovery of sensory nerve function was observed between the groups. The mean durations of the sensory blockade for femoral and sciatic nerves, respectively, was longer (p < 0.001) for group D [168 (146–191, 95% CI), 161 (143–179, 95% CI) min] than in group C [120 (96.1–144, 95% CI), 116 (90.9–142, 95% CI]. No differences in the recovery of patellar and tibial reflexes, proprioceptive function, and ability to walk were found among groups. The overall postoperative rescue analgesia requirement was significantly different (p = 0.019) between groups, with an incidence of 5/10 (50%) dogs in group D and 10/10 (100%) dogs in group C.ConclusionDexmedetomidine administered as a CRI (1 μg/kg/h) combined with local lidocaine increases the duration of the sensory component of the sciatic and femoral nerve blocks and reduces the requirement for additional analgesia during the immediate postoperative hours.